An on-chip test structure to measure the Seebeck coefficient of thermopile sensors. (2nd December 2021) - Huang, Peng; Fu, Jianyu; Lu, Yihong; Liu, Jinbiao; Zhang, Jian; Chen, Dapeng
Abstract: Thermopile sensors have a wide range of applications in consumer and industry. Seebeck coefficient is a basic thermal parameter of thermopile sensors. Extracting the Seebeck coefficient of both materials and thermocouple in thermopile sensors is of great importance. In this work, an on-chip test structure is designed. It consists of a substrate, a framework, supporting legs and a sensitive region which has a resistor serving as both heater and temperature detector. A set of on-chip test structures are fabricated along with a thermopile sensor. Its measurement results are analyzed and compared with apparatus measurement results. These results are consistent with each other, and the validity of structure is verified.